Motivasi Kerja, Disiplin Kerja, Dan Kondisi Lingkungan Kerja Pengaruhnya Terhadap Kinerja Karyawan Pada PT Sayap Mulia Sejahtera (Jank-Jank Wings) - Dewi Ayu Haryani; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to describe work motivation, work discipline, work environment conditions, employee performance and analyze the effect of work motivation, work discipline, work environment conditions on employee performance. This study uses a saturated sample, namely the employees of PT wing Mulia Prosperous, totaling 42 people. Data collection techniques using a questionnaire with a Likert scale. The variable of work motivation is measured using five indicators, five indicators of work discipline, five indicators of working environment conditions, and five indicators of employee performance. The results of this study indicate that simultaneously work motivation, work discipline, working environment conditions have a positive and significant effect on employee performance. The results of this study also indicate that the work motivation variable has no effect on employee performance. The work discipline variable has no effect on employee performance. Variable working environment conditions have a positive and significant effect on employee performance. Keywords : Work Motivation, Work Discipline, Working Environment Conditions, And Employee Performance.